2020
DOI: 10.3390/rs12223715
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire-Detection Method Using DenseNet and CycleGAN Data Augmentation-Based Remote Camera Imagery

Abstract: To minimize the damage caused by wildfires, a deep learning-based wildfire-detection technology that extracts features and patterns from surveillance camera images was developed. However, many studies related to wildfire-image classification based on deep learning have highlighted the problem of data imbalance between wildfire-image data and forest-image data. This data imbalance causes model performance degradation. In this study, wildfire images were generated using a cycle-consistent generative adversarial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 43 publications
(51 reference statements)
0
31
0
Order By: Relevance
“…In terms of particular cases of fire detection based on remote imaging sensing systems and applying CNNs for object detection tasks, we identified two types of recent studies, the first ones classify examples of visible fire from very close distances, such as [39][40][41][42], while the second ones try to detect both fire and smoke columns visible in larger distances [43,44].…”
Section: State Of the Artmentioning
confidence: 99%
“…In terms of particular cases of fire detection based on remote imaging sensing systems and applying CNNs for object detection tasks, we identified two types of recent studies, the first ones classify examples of visible fire from very close distances, such as [39][40][41][42], while the second ones try to detect both fire and smoke columns visible in larger distances [43,44].…”
Section: State Of the Artmentioning
confidence: 99%
“…Before the rise in popularity of deep learning methods, computer vision algorithms leveraging hand-crafted features identified that the visual (e.g., color), spatial, and temporal (i.e., motion) qualities of smoke are essential for the machine detection of wildfires [3,[10][11][12]. More recently, deep learning approaches use a combination of convolutional neural networks (CNNs) [5][6][7][13][14][15][16][17], background subtraction [13,16,18], and object detection methods [4,8,17,19,20] to incorporate visual and spatial features. Long short-term memory (LSTM) networks [4,16] or optical flow [14,18,21] methods have been applied to incorporate temporal context from video sequences.…”
Section: Related Workmentioning
confidence: 99%
“…However, the task proves challenging in real-world scenarios given the transparent and amorphous nature of smoke; faint, small, or dissipating smoke plumes; and false positives from clouds, fog, and haze. While the idea of an automated wildfire smoke detection system has been previously explored, the difficulty of acquiring a large, labeled wildfire smoke dataset has limited researchers to using small or unbalanced datasets [3,4], manually searching for images online [4][5][6][7], or synthetically generating datasets [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies combined image data and artificial intelligence methods to improve the accuracy of forest fire detection or to minimize the factors that cause errors. Damage detection studies often face the problem of data imbalances [27], which previously relied only on images downloaded from the Web and social media platforms [28,29]. Online image databases, such as the Corsican Fire Database, have been used for binary classification as a useful test set for comparing computer vision algorithms [30] but are still not available in MLC.…”
Section: Related Workmentioning
confidence: 99%